Physiological correlates of performance. Case study of a world-class rower - Lacour, J.-R.; Messonier, L.; Bourdin, M. (European Journal of Applied Physiology, 2009)
This report describes the changes in physiological capacity of a heavy-weight rower who obtained seven medals in World Championships and Olympic Games. The investigation was carried out over the last 6 years of the rower`s international competition career in comparison with peer champions, and the following 4 years. Over the first period, maximal oxygen uptake (VO2max) remained above 6 l/min which is an outstanding value. The training load measured over the last 18 months of the period increased from 119 to 142 km/wk of rowing. Four years after the international competition period, VO2maxhad only declined by 3.6% although the training load had declined by 35%. These data suggest that the ability of this rower to compete at top level for years was related to ability to maintain an outstanding VO2max. Gross efficiency and ability to rely on anaerobic glycolysis did not emerge as relevant factors.